Pengaruh Sistem Akuntansi Manajemen terhadap Kinerja Manajerial pada PT. Marajasa - Desy Astrid Anindya - (JEBIM Prima, 2020)
Managerial performance can be achieved by means of managers utilizing the ability to see and take advantage of opportunities, identify problems and select and apply the adaptation process appropriately. Through managerial performance in an organization can maintain the survival of an organization. The management accounting system is a formal system designed to provide information to managers. The purpose of this study was to examine the effect of the Management Accounting System on managerial performance. The population in this study were managers and assistant managers at PT. Marajasa, amounting to 31 people and the sample is a saturated sample, namely 31 respondents. The data analysis technique used in this study used regression analysis to answer the research objectives. The results showed that the management accounting system had an effect on managerial performance